Limpets compensate sea urchin decline and enhance the stability of rocky subtidal barrens. (April 2016) - Piazzi, Luigi; Bulleri, Fabio; Ceccherelli, Giulia
Abstract: Understanding the mechanisms that regulate shifts among alternative ecosystems has become a priority for ecologists and environmental scientists. This study assessed the relative importance of different herbivorous invertebrates (urchins and limpets) in regulating transitions from barren to vegetated states on Mediterranean rocky reefs, under different levels of nutrient availability. Nutrient concentration and the herbivore assemblage were manipulated to test i) whether limpets can compensate for the decline or loss of sea urchin populations, thereby contributing to the persistence of barrens, ii) whether limpet effects vary according to nutrient availability and iii) whether limpets affect the structure of the algal assemblage. The complete removal of sea urchins was not sufficient to trigger the recovery of erect and turf-forming macroalgae if limpets were left at natural density, suggesting that these herbivores play an important role in the stability of the barren state. The effect of these mesograzers was particularly important under oligotrophic conditions. This suggests that limpets play an important role in sustaining the stability of the barren state. A more comprehensive assessment of top-down forces, implying the quantification of the relative effect of different herbivore guilds, is therefore necessary to estimate the strength of hysteresis and to identify critical thresholds at which shifts back to the vegetated state are initiated. Highlights: The study investigated transition from barren to vegetated state on rocky habitat. The study assessed the role of herbivores and nutrients in macroalgal recovery. Sea urchins removal was not sufficient to trigger the recovery of vegetated state. Limpets play an important role in the stability of the barren state. The effect of limpet was especially important under oligotrophic conditions.